2011
DOI: 10.1186/1471-2164-12-576
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of the type VI secretion systems of Pantoea and Erwinia species reveals the presence of putative effector islands that may be translocated by the VgrG and Hcp proteins

Abstract: BackgroundThe Type VI secretion apparatus is assembled by a conserved set of proteins encoded within a distinct locus. The putative effector proteins Hcp and VgrG are also encoded within these loci. We have identified numerous distinct Type VI secretion system (T6SS) loci in the genomes of several ecologically diverse Pantoea and Erwinia species and detected the presence of putative effector islands associated with the hcp and vgrG genes.ResultsBetween two and four T6SS loci occur among the Pantoea and Erwinia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
106
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(110 citation statements)
references
References 53 publications
3
106
0
1
Order By: Relevance
“…Commonly, these 'orphan' hcp and vgrG genes are always encoded in the proximity of putative effector genes. 30,31 Further studies demonstrated that in T6SS-dependent delivery, the antibacterial effectors are loaded onto the secretion complex by interaction with PAAR/VgrG or by binding to the inner surface of the Hcp tube. 3 Notably, some VgrG and PAAR proteins can carry antibacterial extension domains, thus acting as secreted T6SS effectors.…”
Section: Nad (P)mentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly, these 'orphan' hcp and vgrG genes are always encoded in the proximity of putative effector genes. 30,31 Further studies demonstrated that in T6SS-dependent delivery, the antibacterial effectors are loaded onto the secretion complex by interaction with PAAR/VgrG or by binding to the inner surface of the Hcp tube. 3 Notably, some VgrG and PAAR proteins can carry antibacterial extension domains, thus acting as secreted T6SS effectors.…”
Section: Nad (P)mentioning
confidence: 99%
“…31,32 The VgrG and PAAR proteins have been demonstrated to carry diverse C-terminal extension domains functioning as T6SS antibacterial effectors, 6,16,32 while the toxic domains fused to Hcp proteins have never been verified to mediate interbacterial antagonism. Our comparative genomics analysis identified an extended Hcp with a C-terminal HNH-DNase toxin domain (ET-toxin) in human O104 Shiga toxin-producing E. coli (STEC) strain C227-11 and piglet diarrhea isolate STEC004 (Fig.…”
Section: A C-terminal Toxin Domain Carried By An Extended Hcp Exhibitmentioning
confidence: 99%
“…Comparative genomic analysis of Pantoea species have demonstrated the presence of up to three gene clusters, designated T6SS-1 through T6SS-3, encoding components of the T6SS (De Maayer et al 2011). Subsequent comparative genomics of sequenced P. ananatis strains indicated that the T6SS-1 and T6SS-3 gene clusters are present in all strains analyzed, whereas the T6SS-2 gene cluster is present in some but not all of these strains (Shyntum et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the coordinated functions of VipA, VipB, and ClpV are needed for active secretion. In most T6SSs, hemolysin-coregulated protein (Hcp) and valine-glycine repeat protein G (VgrG) are exported by the secretion machinery, but most likely numerous other proteins are secreted as well (30)(31)(32)(33)(34)(35)(36). The well-characterized Hcp protein is not only secreted but also suggested to be a chaperone that binds to cognate T6SS effector molecules, and it forms a hexameric pore that is required for secretion of diverse effectors encompassing several enzymatic classes (37)(38)(39).…”
mentioning
confidence: 99%